The slow structuring of the church through instruction and Council of Lima 1545, sixteenth century - León Fernández, Dino (2014)
The first two Councils Limenses thus laid the foundation of the church in the Andes and determined the broad guidelines to be followed by all who profess the Catholic faith. e prelates and ocials proclaim the rules to be observed by the Indians who received baptism, and cared for those who were not yet baptized. is attempt of adaptation is re ected in the norms issued by the said Council in the part concerning the evangelization of the natives. And the main task of the third Council is the importance given to the Catechism, Confession and Sermonario